CGIAR Multifunctional Landscapes at COP30: Advancing Adaptation and Nature-Based Solutions - Edward-Uwadiale, Regina (CGIAR System Organization, 2025)
This article by Regina Edward-Uwadiale highlights CGIAR’s engagement at the 2025 United Nations Climate Change Conference (COP30) in Belém, Brazil, focusing on how multifunctional landscapes contribute to climate adaptation and nature-based solutions. It reports on CGIAR’s participation in side events and sessions at the joint CGIAR–FAO Food and Agriculture Pavilion, where scientists and policymakers shared evidence of integrated landscape approaches such as climate-resilient farming, agroforestry, agrobiodiversity conservation, and circular bioeconomy practices that restore ecosystems, strengthen rural livelihoods, and support adaptation goals under the Global Goal on Adaptation. The article outlines specific events hosted by CGIAR showcasing how these solutions align with adaptation indicators and discusses CGIAR scientists’ wider involvement in panels and dialogues across COP30 to inform global climate policy and scale practical pathways for resilient food and land systems.